2005
DOI: 10.1002/ejoc.200500550
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Controlling the Central Torsion Angle in Biphenyl‐Based Molecular‐Scale Bridges

Abstract: The synthesis of a series of crown ether ligands (C4-C6) based upon the 2,2Ј-biphenyl unit is described. In the series, the length of the polyether chain connecting the two oxygen atoms increases progressively. These polyethers are moderately fluorescent in acetonitrile solution, but this emission is partially quenched upon the addition of various alkali metal cations. Spectrofluorimetric titrations performed with MClO 4 (M = Li + , Na + ) or KPF 6 show that binding to crown ethers C4-C6 involves the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…Details of the photophysical properties of the binuclear Ru-Ru complexes are available in the literature, [17] as is a separate study of cation binding. [18] The absorption spectra of the various mixed-metal complexes are essentially superimposable and the characteristic features of a metal-polyA C H T U N G T R E N N U N G (pyridine) complex are easily recognized. For the mixed-metal complexes, there is a pronounced spin-forbidden transition at wavelengths longer than 600 nm that can be used for selective excitation into the Os-terpy unit (terpy = 2,2':6',2''-terpyridine).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the photophysical properties of the binuclear Ru-Ru complexes are available in the literature, [17] as is a separate study of cation binding. [18] The absorption spectra of the various mixed-metal complexes are essentially superimposable and the characteristic features of a metal-polyA C H T U N G T R E N N U N G (pyridine) complex are easily recognized. For the mixed-metal complexes, there is a pronounced spin-forbidden transition at wavelengths longer than 600 nm that can be used for selective excitation into the Os-terpy unit (terpy = 2,2':6',2''-terpyridine).…”
Section: Resultsmentioning
confidence: 99%
“…To summarize the findings, the ES mass spectral records confirmed a metal:ligand ratio of 1:1 across the whole cation series, with no sign of higher order assemblies. The association constants for the ligands towards the various cations in acetonitrile, as measured by fluorescence quenching experiments, [18] were in the order of 3-7500 m…”
Section: Methodsmentioning
confidence: 99%
“…[4] The results of studies on these biphenyl derived ligands have demonstrated that conformational changes induced by modification of the dihedral angle of the biphenyl moiety have a strong influence on the fluorescent properties of the sensor. [5] The development of new sensor systems has prompted us to synthesize new ligands. As a result of its interesting characteristics [6] and, more importantly, its analogy to the biphenyl system, bipyridine seemed an interesting target for a transducer subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Planar geometries favour higher yields and longer lifetimes. 4 For all these reasons, we have been interested in using the 4,4'-bis(N,N-dimethylamino)biphenyl (TMB, tetramethylbenzidine) subunit in the design and synthesis of red-ox and fluorescent sensors. 5 TMB-derivatives ligands show very peculiar fluorescent properties.…”
mentioning
confidence: 99%